FACING THE INTELLECTUAL AND CULTURAL CHALLENGES AMONG THE MUSLIM UMMAH IN THE 21ST CENTURY - Ahmed Mohamed, Ismaiel Hassanein (2018)
1. Overview of the Fourth Industrial Revolution 2. Industrial Revolution Implications on people 3. IR4 impact on the Muslim ummah 4. Intellectual and culturalChallenges in the Muslim ummah